Myth, Sense, Work: Garroni and the crisis of contemporary arts - D'Ammando, Andrea (Aesthetica Preprint, 2022)
Sense, as an issue, represents the philosophical problem that Garroni most deeply thought about throughout his long practice of study and reflection. The problem of the conditions of the sense of experience, as in the indeterminate condition of our determinate knowing and speaking, arises as a central issue in Garroni’s works in the wake of the profound rethinking of Kantian critical philosophy opened in 1976 by the writing Estetica ed Epistemologia. It is, however, already present in his earliest works, and runs through all Garroni’s philosophical production. This problem is linked to another important notion: the crisis itself would later be revived and discussed by Garroni in the following decades. As a matter of fact, during the 1960s, Garroni’s studies focused on the semantic crisis of the arts and the problem of a “rational myth.” Also in this case, it is not difficult to recognize its centrality to the crisis’s theme. The idea of the crisis of modern and contemporary art is also present in Garroni’s mature thinking, albeit in a different way. In this regard, “crisis”, like “sense” (and “horizon”), is a word dear to Garroni’s thought, at least in terms of the problem of art and its very uncertain and problematic status. During the second half of the twentieth century, art was deeply marked by the crisis of form and of the very idea of ‘work’: a crisis that concerns, precisely, the sense and problem of the exemplarity of art.